Antisipasi Rencana Pembayaran Hutang Dagang Melalui Pengukuran Translation Exposure dengan Metode Current Rate dan Penggunaan Forward Contract Hedging - Soelehan, Aan; Marpaung, Annaria Magdalena; Dewi K., Shanty (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
Translation exposure is the exposure of profit and loss balance sheet at a multinational company on nominal exchange rate. The potential of risk translation is used to measure change of foreign currencies exchange rate on domestic currency value of assets and foreign currencies owned by the company. Translation exposure is measured by current rate method and business debt is anticipated by forward contact hedging. The purpose of this research is to find out the risk level of translation exposure by current rate method, the management of current rate method itself, and the management of forward contract to business debt anticipation. The analysis method used is current rate measurement method, forward contract hedging calculation, and relevant variables management. The results show that for current rate measurement at PT Panasia Filament Inti Tbk., viewed from 2005 – 2009, YEN currency has the highest translation exposure percentage value and gets loss in translation exposure; for forward contract hedging calculation, viewed from 2005 – 2009, all currencies namely GBP, EURO, USD, CHF, SGD, and YEN have various profit and loss from forward contract itself. Keywords: translation exposure; current rate method; forward contract hedging; business debt